Sports Event Sponsorship in Increasing L-Men Brand Awareness and Brand Trust - Jose, Fernando; Valdez, Mohamad Alppy (Peneliti.net, 2025)
To differentiate from competitors, several business marketing activities must be executed. One of them is through being a sponsor in events that share the same values. L-Men, has also implemented event sponsorship as one of its marketing activities. The study aimed to determine the effect and how much influence ASEAN Para Games 2022 event sponsorship has towards L-Men brand awareness and brand trust for L-Men Instagram followers. This study uses the S-O-R theory and the quantitative research method. The research sample was collected using simple random sampling, with the questionnaire distributed via Google Forms to 100 people who are part of L-Men Instagram followers and aware of the ASEAN Para Games 2022, using the Likert scale for the measurement reference. The result of this research illustrates that there is almost no influence between the ASEAN Para Games 2022 event sponsorship and L-Men brand awareness with only 2,4% contribution value, while there is an influence between the event sponsorship and L-Men brand trust with 42% contribution value. This research is expected to be an input for the research object and other similar brands to accelerate their marketing strategy to increase either brand awareness or trust